The reliability of data integriti preservation in archival institutions / Normashidayu Abu Bakar and Nordiana Mohd Nordin - Abu Bakar, Normashidayu; Mohd Nordin, Nordiana (Faculty of Information Management, 2022)
Digital preservation is a broad term that includes everything that needs to be done to keep digital materials accessible even if the media fail or technology changes. The advent of digital storage has profoundly altered our surroundings. Data is growing in size, thus individuals are migrating their data to the digital. This research will identify the factors that influence digital preservation, identify the benefits of digital preservation in archival institutions, measure the extent of digital preservation among members of archival institutions, and identify the data integrity of digital preservation in National Archives of Malaysia.